Issr Markers Assisted Studies On Genetic Diversity In Brassica Juncea - MANJU YADAV,; J. S. RANA, (International Journal of Pharma and Bio Sciences, 2012)
Genetic polymorphism was studied among thirty Indian mustard genotypes using 20 ISSR primers. This study revealed 156 amplified bands with an average of 7.8 bands per primer out of which 115 were polymorphic. Size of amplified fragments ranged from 100 bp to 1500 bp and number varied from 4 to 14. ISSR data were used to compute genetic similarities based on Jaccrad’s similarity coefficient, it ranged from 0.50 to 1.0. Similarity matrix was utilized to construct the UPGMA (unweighted pair- group method with arithmetic average) dendrogram. In cluster analysis, based on similarity coefficient, Indian mustard genotypes were categorized into three major clusters Two dimensional and three dimensional analyses further strengthened the cluster analysis observations. Genotypes, Kranti and Rohini were found to be least diverse. BEC 144 was most diverse genotype with a separate cluster. Phenotypic variation was also analyzed and revealed some genetic relationship among genotypes which were evaluated for seed yield and other phenotypic traits.